Sustainable irrigation and abiotic tolerant crops in South Italy within TRUSTFARM project - Cataldo Pulvento; Osama Ahmed; Mohamed Houssemeddine Sellami; Antonella Lavini; Giuseppe De Mastro (Environmental Sciences Proceedings, 2022)
Today, irrigated agriculture is even more influenced by climate change with consequent negative effects on food security. The Mediterranean area is most affected by climate change, leading to greater exposure to uncertainty and production risks. In these environments, water stress, rainfall variability, and soil salinization have been accentuated. Improving crop productivity by minimizing such effects is possible through intelligent climate farming practices (CSFP). Towards resilient and sustainable integrated agro-ecosystems through appropriate climate-smart farming practices (TRUSTFATM) is a project funded by the European Union's Horizon 2020 research and innovation program with the aim to design integrated agro-ecosystems by conserving natural resources and using the principles of the circular economy for developing climate-resilient production systems in Egypt, Morocco, Italy, France, and Senegal. The Department of Agricultural and Environmental Science (DISAAT) of the University of Bari is responsible for coordinating the activities (starting in 2022) related to the introduction of new crop varieties and management of water and efficient irrigation systems, such as deficit irrigation, use of marginal quality (saline water) irrigation water, and introduction of abiotic stress-tolerant crops.
Keywords: 330; salinity; climate change; tolerant crops